Immobilization of microalgae cells in alginate facilitates isolation of DNA and RNA (2017)
Isolation of nucleic acids from Chlorella is difficult, given the chemically complex nature of their cell walls and variable production of metabolites. Immobilization of microalgae in polymers adds additional difficulty. Here, we modified, amended, and standardized methods for isolation of nucleic acids and compared the yield of DNA and RNA from free-living and encapsulated microalgae C. sorokiniana. Isolation of nucleic acids from immobilized cells required two steps in dissolving the alginate matrix, releasing the cells, and mechanical disruption with glass beads. For DNA extraction, we used modified versions of a commercial kit along with the hexadecyltrimethylammonium bromide (CTAB) method. For RNA extraction, we used the commercial TRI reagent procedure and the CTAB-dithiotreitol method. Quantity and quality of nucleic acids in extracts varied with growth conditions, isolation procedures, and time of incubation of the original culture. There were consistently higher amounts of DNA and RNA in extracts from immobilized cells. Quantitatively, the modified procedure with the commercial Promega kit was the most reliable procedure for isolating DNA and a modified commercial TRI reagent procedure was the choice for isolating RNA. All four procedures eliminated proteins efficiently and had low levels of contamination from residual polysaccharides from the matrices and/or metabolites naturally produced by the microalgae. All DNA extracts under both growth conditions, time of incubation, and two isolation methods successfully amplified the 18S ribosomal RNA by PCR and quantitative reverse transcription (RT-qPCR).